Analisis Swot Untuk Menentukan Strategi Pengembangan Potensi Wisata Grojogan Asmoro Desa Jarak - Dhian Satria Yudha Kartika; Cahya Maghfira Prasetya; Vani Laila; Hafsha Sakinah; Ripka Suliandari (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Jombang Regency is an area that has a lot of tourism potential, for example in Wonosalam District. This sub-district has a variety of natural potentials, one of which is the potential for nature tourism, namely Grojogan Asmoro which is located in the village of Distance. However, to develop this tourism potential, the right strategy is needed so that it can become a tourist attraction. In addition, the management of a Grojogan Asmoro tourist attraction requires the involvement and active participation of local human resources. This study uses a descriptive research method with a qualitative approach. The use of data in this study is primary data and secondary data. In the process of identifying the tourism potential of Grojogan Asmoro, a SWOT analysis was used to describe the tourism potential, then formulate a strategy for developing waterfall tourism potential. The Grojogan Asmoro tourism development strategy plan is to develop and improve various components which include accessibility, facilities, and environmental preservation in the waterfall area to increase tourist attraction. This is to the concept of tourism, namely ecotourism (ecotourism). The concept of ecotourism is a concept that aims to develop a tourist area but is still responsible for the surrounding natural areas to support people's welfare. Thus, this study aims to analyze and identify the tourism potential in Grojogan Asmoro and determine a tourism development strategy that is appropriate to the conditions in Grojogan Asmoro.